DERL3 facilitates the progression of clear cell renal cell carcinoma by promoting epithelial-mesenchymal transition via regulation of the TGFB1 pathway - Chengtao Niu; Haodong Cui; Xintong Sun; Yuchang Yang; Xue Jiang; Zixiang Cong; Yiming Zhang; Zhihong Niu; Wei He (PLoS ONE, 2025)
Background Clear cell renal cell carcinoma (ccRCC) is a highly prevalent malignancy within the urinary system. The intrinsic heterogeneity and resistance to conventional chemotherapy and radiotherapy contribute to the poor prognosis of advanced ccRCC patients. DERL3, part of the Derlin protein family, was first identified for its critical role in endoplasmic reticulum stress. Subsequent studies have revealed its involvement in the progression of multiple tumor types; however, its role in ccRCC remains unclear. Methods In this study, we utilized bioinformatics analysis and in vitro experimental approaches to investigate the role of DERL3 expression in the metastasis of renal clear cell carcinoma cells. Additionally, we analyzed the correlation between DERL3 expression and the prognosis of renal clear cell carcinoma patients, while exploring its potential mechanisms of action. Results We demonstrate for the first time that DERL3 promotes tumor progression in ccRCC, showing significantly elevated expression, especially in metastatic ccRCC cell lines. Further studies suggest that this overexpression of DERL3 may promote the epithelial-mesenchymal transition in ccRCC by upregulating TGF-β1, thereby enhancing ccRCC metastasis. Conclusion In conclusion, our study clarifies the role and potential mechanisms of DERL3 in ccRCC progression, providing promising therapeutic avenues for improving the prognosis of ccRCC patients.